Chemical functionalization of polyethylene surfaces by plasma-assisted carbene insertion. Issue 12 (2nd December 2017) - Hu, Zhen; Moloney, Mark G.; Parker, Emily; Chng, Shuyun; Wu, Linda Y. L.
ABSTRACT: Controlled surface modification of PE is achieved by an efficient and facile approach via plasma-assisted carbene insertion generated using diazo chemistry. The combination of plasma and carbene insertion shows a synergistic effect, which leads to an obvious enhancement of surface grafting, as shown qualitatively by a combination of IR and UV reflectance spectroscopy, and XPS analysis. The chemical modification may be observed spectroscopically, and the approach provides an opportunity for the convenient modification of low surface energy materials.